The Role of Stimuli Complexity and Handedness on Visual Symmetry and Asymmetry Preference (European Journal of Behavioral Sciences, 2021)
Previous research results indicate visual information processing asymmetry in case of visual verbal stimuli. However, other studies that investigate nonverbal stimuli processing show inconsistent effect of laterality. Although differences between left- and right-handers can be found in tasks that involve letters, spatial attention stimuli and visuomotor control performance, the differences between the two groups almost disappear in several directional preference tasks, suggesting that direction preference is influenced mainly by writing and reading habits. Perceiving visual art involves visual attention, that is driven by the bottom-up aspects of the visual stimuli, therefore perception of nonverbal images, that contain geometrical forms might be influenced by handedness. To assess the possible differences in visual symmetry- asymmetry preference, university students (N = 65) were divided into two groups based on handedness, and as a measurement we used simple- complex- symmetrical and asymmetrical geometrical forms. Our main result shows a significant effect of stimuli complexity on symmetry-asymmetry preference. The interaction effect between handedness and symmetry-asymmetry type was not significant. After conducting a pairwise comparison our results show that right-handers evaluate simple and complex symmetrical forms as more preferable than simple and complex asymmetrical forms. We also found that there is a preference for symmetry over asymmetry in both groups, however these differences are significant only in the right-handed group. We conclude that preference for symmetrical geometrical forms is not influenced by handedness, however preference for complexity is affected by right-handedness. To extend these results, further investigations are needed.